EFFORTS TO IMPROVE MASK USE AS A PREVENTIVE MEASURE AGAINST RESPIRATORY INFECTIONS AMONG WORKERS AT THE OPAK GADUNG FACTORY IN KEDIRI REGENCY - Irianingtyas, Riza; Eka Nur Rahmania, Nima; Setya Maryiantari, Ellyza (Community Service Journal of Indonesia, 2025)
Respiratory tract infections are common among informal workers who are exposed to dust, smoke, and airborne particles during production activities. This community service program aimed to improve workers’ knowledge regarding the importance of using masks as a preventive measure against respiratory infections. Health education was delivered through counseling, discussion, and demonstration to 12 workers Opak Gadung factory, Desa Ringinsari, Kediri. Knowledge was assessed using pre- and post-tests. The results showed a significant increase in the average knowledge score from 52.50 to 79.90, with a p-value of 0.000, indicating that the educational intervention was effective. This activity successfully enhanced workers’ awareness and proper mask-use practices. Continuous education programs are recommended to support occupational health and safety in informal workplaces.